2004
DOI: 10.2337/diacare.27.6.1294
|View full text |Cite
|
Sign up to set email alerts
|

Younger Age at Onset and Sex Predict Celiac Disease in Children and Adolescents With Type 1 Diabetes

Abstract: OBJECTIVE -To estimate the prevalence of biopsy-confirmed celiac disease in Italian children and adolescents with type 1 diabetes and to assess whether age at onset of type 1 diabetes is independently associated with diagnosis of celiac disease.RESEARCH DESIGN AND METHODS -The study group was a clinic-based cohort of children and adolescents with type 1 diabetes cared for in 25 Italian centers for childhood diabetes. Yearly screening for celiac disease was performed using IgA/IgG anti-gliadin and IgA anti-endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
143
8
11

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(184 citation statements)
references
References 24 publications
22
143
8
11
Order By: Relevance
“…In Italy, the prevalence of celiac disease in children with type 1 diabetes is around 7% [9,10] , 3.6% of which at type 1 diabetes onset [9] , at a younger age [10] and in boys [10] ; moreover, according to a study by Salardi et al [11] , the prevalence of celiac disease has significantly increased since 1994 (10.6% vs 6.6%, P = 0.015), probably due to changes in environmental factors, namely, eating habits and viral infections.…”
Section: Introductionmentioning
confidence: 99%
“…In Italy, the prevalence of celiac disease in children with type 1 diabetes is around 7% [9,10] , 3.6% of which at type 1 diabetes onset [9] , at a younger age [10] and in boys [10] ; moreover, according to a study by Salardi et al [11] , the prevalence of celiac disease has significantly increased since 1994 (10.6% vs 6.6%, P = 0.015), probably due to changes in environmental factors, namely, eating habits and viral infections.…”
Section: Introductionmentioning
confidence: 99%
“…La frecuencia de EC en pacientes con DM1 en nuestro estudio es un porcentaje alto (9,4%), en [4][5][6][7][8][9] comparación con otros estudios que varía entre 1 a 8%. Un estudio realizado en el Brasil encontró una 4 5 prevalencia del 2,5% , mientras que otro en España halló una prevalencia del 8% , existiendo series que 7 muestran prevalencia de hasta 12% .…”
Section: Discussionunclassified
“…Development of CD can occur at any age but usually takes place within 5 years of diagnosis of T1DM. Cerutti et al 28 suggested that the highest risk of developing CD in children diagnosed with T1DM was under 4 years of age and the risk was much lower in children of school going age and older children. An epidemiological study from Australia reported that CD is common in young patients with young age of onset of diabetes (< 5years of age) and longer duration of diabetes mellitus.…”
Section: Coeliac Diseasementioning
confidence: 99%